Atomic Structure Modification of Fe‒N‒C Catalysts via Morphology Engineering of Graphene for Enhanced Conversion Kinetics of Lithium–Sulfur Batteries. (26th January 2022) - Kim, Jiheon; Kim, Seong‐Jun; Jung, Euiyeon; Mok, Dong Hyeon; Paidi, Vinod K.; Lee, Jaewoo; Lee, Hyeon Seok; Jeoun, Yunseo; Ko, Wonjae; Shin, Heejong; Lee, Byoung‐Hoon; Kim, Shin‐Yeong; et al.
Abstract: Single‐atom M‒N‒C catalysts have attracted tremendous attention for their application to electrocatalysis. Nitrogen‐coordinated mononuclear metal moieties (MNx moities) are bio‐inspired active sites that are analogous to various metal‐porphyrin cofactors. Given that the functions of metal‐porphyrin cofactors are highly dependent on the local coordination environments around the mononuclear active site, engineering MNx active sites in heterogeneous M‒N‒C catalysts would provide an additional degree of freedom for boosting their electrocatalytic activity. This work presents a local coordination structure modification of FeN4 moieties via morphological engineering of graphene support. Introducing highly wrinkled structure in graphene matrix induces nonplanar distortion of FeN4 moieties, resulting in the modification of electronic structure of mononuclear Fe. Electrochemical analysis combined with first‐principles calculations reveal that enhanced electrocatalytic lithium polysulfide conversion, especially the Li2 S redox step, is attributed to the local structure modified FeN4 active sites, while increased specific surface area also contributes to improved performance at low C‐rates. Owing to the synergistic combination of atomic‐level modified FeN4 active sites and morphological advantage of graphene support, Fe‒N‒C catalysts with wrinkled graphene morphology show superior lithium–sulfur battery performance at both low and high C‐rates (particularly 915.9 mAh g −1 at 5 C) with promising cycling stability. Abstract : Atomic‐level engineering of MNx active sites is a desirable strategy to enhance and fine‐tune electrocatalytic performance of M‒N‒C catalysts. FeN4 active sites on wrinkled graphene support exhibits different structural and electronic properties compared to square‐planar FeN4 moieties. The synergistic combination of modified FeN4 active sites and morphological advantage of wrinkled graphene support improves the electrocatalytic performance for lithium–sulfur conversion chemistry.